Pengaruh Kualitas Pelayanan terhadap Kepuasan Anggota Perpustakaan pada Dinas Kearsipan dan Perpustakaan Kabupaten Paser - Amir Hamzah (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to determine the simultaneous and partial influence as well as the dominant variables of Service Quality (X) which include the variables Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), Physical Evidence (X5), on Satisfaction of Library Members (Y) at the Paser Regency Archives and Library Service. From the results of the validity test of the total number of questions, 18 statements all have a value of rcount > rtable, which means all questions are valid (feasible). From the results of the reliability test, it can be seen that the results obtained were 0.836, which means that the questionnaire items can be said to be reliable, because the Cronbach's Alpha value is > 0.6. From the results of multiple linear regression analysis research, the regression equation Y= 0.465 + 0.366X1 + 0.265 X2 + 0.183 X3 - 0.185X4 + 0.246 X5. The correlation coefficient (R) is 0.843 at a relationship level of 0.80-1.000, which means it is at a very strong relationship level between the variables Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), Evidence Physical (X5), to Member Satisfaction (Y). The Adjusted R square value (coefficient of determination) is 0.503, which means that the Service Quality (X) variable consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4) and Physical Evidence (X5) contributes of the dependent variable, namely Member Satisfaction (Y), while the remaining 49.7% is influenced by other variables not included in this research. From the results of the F test, the Fcount value is 14.372 > Ftable 2.37, so it can be concluded that the Service Quality (X) variable consists of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4) and Physical Evidence ( X5) has a significant effect simultaneously (together) on the Member Satisfaction variable (Y), so that the first hypothesis can be accepted or H0 is rejected. Ha is accepted. From the results of the t test for the variables Reliability (X1), Responsiveness (X2), and Physical Evidence (X5) have a significant effect on Member Satisfaction (Y) of libraries at the Paser Regency Archives and Library Service. Meanwhile, the variables Assurance (X3), Empathy (X4) do not have a significant effect on Library Member Satisfaction (Y) at the Paser Regency Archives and Library Service. Furthermore, the t test results show that the Reliability variable (X1) has a dominant influence on Member Satisfaction (Y) which is strengthened by the highest t value of 3.299 and a significance value of 0.002. So the hypothesis states that it is not proven or rejected. H0 is accepted. Ha is rejected.